역삼투법 해수담수화 전처리 여과공정의 최적조건 - 김승현; 윤종섭; 이석헌 (대한상하수도학회, 2009)
This study examines the optimum filtration conditions in pretreatment of seawater desalination by reverse osmosis. For this purpose, Masan bay seawater is treated through a gravity filter column while FeCl3 is added as coagulant. The conditions of coagulantd osage, media depth, filtration rate, and backwash time are evaluated. The study results show that the filtrate quality improved with increasing coagulant dosage, but head loss rapidly increased. After 4mg/L, the unit filter run volume reduced to less than 200㎥/㎡. Considering the head loss development, 4mg/L is determined as the optimum dosage. The better filtrate qualities are obtained with depth of 100cm than that of 80cm. The two stage filtration, which outperformed the single stage filtration, is suggested for treatment of Masan bay. The filtration rate of 5m/h is decided as the optimum condition considering the head loss development. At 10m/h, the filtrate quality deteriorated even though the extent was minimal, and head loss increased rapidly. The backwash time of 10 min is decided appropriate.